Histomorphologic study of giant cell lesions of the jaws and giant cell tumour of bone - Akinyamoju, Akindayo Olufunto; Okiti, Robinson Obos; Adisa, Akinyele Olumuyiwa; Lawal, Ahmed Oluwatoyin (Journal of Oral Diagnosis, 2025)
Objective: This study aimed to determine the cytometric differences in giant cell lesions of jaws (GCLs) and giant cell tumour of bones (GCTB). Methods: This was a retrospective study where histology of GCLs and GCTB were reviewed to determine number of giant cells per 5 high power field (5HPF) and nuclei number per giant cell by manual counting. Data were analyzed using SPSS version 23. Chi-square test was used to determine association between variables. The level of significance was set at p<0.05. Results: Forty-five cases were analysed, 17 males (37.8%) and 28 females (62.2%) with a M: F of 1.0:1.7. The mean age was 27.1±11.8 years while peak age of occurrence was the third decade of life. The mandible and associated gingivae (20/44.4%) were the most affected sites, followed by long bones with 14 (31.2%) cases. Mean number of giant cells per 5 HPF in central giant cell granuloma (CGCG) and GCTB was 10.0±3.5 and 10.5±4.19 respectively (p=0.67). Mean number of nuclei per giant cell was 12.8±3.8 in CGCG and 14.6±3.2 in GCTB (p=0.51). Conclusion: GCTB and CGCG cannot be differentiated by cytometric parameters alone. Standardized methods for assessing cytometric differences are advocated, to allow for better comparison.